Protein folding - Campeotto, Ivan (Henry Stewart Talks, 2025)
Protein folding and Protein misfolding, Protein folding diseases, Predicting protein structure, Homology modeling, Energy landscape of protein folding, 3D structure, CASP, Rosetta software, Alpha helix and Beta sheet, Coiled coil